Dampak Media Sosial Instagram Pada Kawasan Smart Heritage Market Pasar Badung - Ni Made Rinayanthi; Utik Kuntariati (UNHI Press, 2023)
The use of social media today is enormous, almost all circles use social media both in terms of communication and obtaining a variety of information. This is marked by the easiness of accessing information through digital media. Pasar Badung is the largest market in Bali, located in the center of Denpasar on Jalan Gajah Mada. The concept of market digitization and smart heritage market embedded in Pasar Badung facilitates interaction between sellers and buyers. The free Wifi in this market can be used as a promotional vehicle for sellers to introduce their products to buyers or tourists. The purpose of this study was to determine how the impact of social media Instagram on interest in visiting the Smart Heritage Market Pasar Badung Denpasar area. This study was designed using quantitative methods with multiple linear regression analysis. This study focuses on social phenomena and on giving a voice to the feelings and perceptions of informants. The population in this study is the number of followers taken from two Instagram accounts, namely; @InfoDenpasar as many as 1.000.000, and @DenpasarTourism as many as 4.480 followers, while from Tagar (#), there were 14.000 tags/posts from #pasarbadung and 1000 tags/posts from #tukadkorea with a sample of 155. The results showed that the use of social media Instagram was from general characteristics respondents indicated by males aged 17-30 years, the majority of whom live in Bali. Instagram has a real effect or impact on visiting interest. Based on the analysis of the five dimensions of the role of social media Instagram, namely participation, openness, conversation, community, and connectedness, where conversation, community, and connectedness are combined in one dimension, namely communication, communication dimensions, and openness are very influential on visiting decisions.